Expression analysis of COMMD5, NPPA, SLC7A1 and AT1R genes among hypertensive Malays - Bdair, Ban Waheed Hussein (2017)
Hypertension is one of the most common and known risk factors for cardiovascular disease. This disease affects structures and functions of small muscles arteries, arterioles and other blood vessels. It is known to cause varying damages in different organs like brain, eye and kidney which may eventually lead to stroke, poor vision and renal disease. By 2025, it has been predicted that about 1.56 billion people are expected to have high blood pressure. Recently, Global Burden of Disease reported high-level blood pressure as the most significant risk factor for mortality. In the year 2011, National Health Morbidity Survey (NHMS) IV reported 32.7% as the prevalence rate of hypertension in Malaysia. Environmental risk factors such as sedentary lifestyle, dietary factors, smoking, and lack of physical activity in combination with genetic factors play important role in progression of hypertension. Of recent, human genetic studies have reported several candidate genes such as COMMD5 (COMM Domain-Containing Protein 5), which relates with calcium haemostasis and NPPA (Natriuretic Peptide A), a gene that play key roles in maintenance of cardiovascular homeostasis as well as vasodilation. Similarly, the SLC7A1 (solute carrier family 7 member 1) gene which is involved in the transport of the cationic amino acids (arginine) and AT1R (Angiotensin II Receptor Type 1) that controls blood pressure/ volume in the cardiovascular system are also potent candidate genes. Although the functions of these genes have been identified, there is absence of detailed comprehensive analysis of the expression of these genes collectively in association with hypertension among Malays. In line with this, the present study aimed at determining the expression level of these genes (COMMD5, NPPA, SLC7A1, and AT1R) among hypertensive Malay subjects. Therefore, a total of 100 newly diagnosed hypertensive patients and 100 unrelated healthy individuals were recruited. Total RNA was extracted from whole blood specimen using RNA extraction kit and the target genes were quantitated using Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). General Linear Model analysis was performed using SPSS software and p≤0.05 was deemed significant and analysis of gene expression and relative expression in qPCR was performed using REST software. The demographic characteristic of the subject such as body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), low density lipoprotein (LDL), triglyceride (TG) and cholesterol (Chol) were shown to be differently significant (p<0.05) in experimental subjects compared to control. Moreover, age and high density lipoprotein (HDL) did not show any significance (p>0.05). Gene expression pattern was determined in hypertensive patients and compared with control. COMMD5 and AT1R genes were significantly upregulated in hypertensive patients compared with control (p<0.05), while SLC7A1 and NPPA genes were downregulated in hypertensive patients compared with healthy individuals. This study demonstrated that COMMD5, NPPA, SLC7A1, and AT1R might be involved in pathogenesis of hypertension, and hence could be used as diagnostic biomarkers in the prediction of hypertension in Malay subjects.